Pelatihan Kewirausahaan Berbasis Digital Pada Santri di Pondok Pesantren Al Majidi Desa Banyukapah Kabupaten Sampang - Rodiaminollah, Moh.; Ali Fahmi, Moh. (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2023)
Digital-based entrepreneurship training carried out at the Al Majidi Islamic Boarding School, Banyukapah Village, Sampang Regency, has the main aim of improving the students' ability to utilize digital technology to develop their businesses. In the current digital era, understanding entrepreneurship and the ability to adapt to technology is very important, especially for the younger generation who want to start an independent business. This training focuses on This training is designed to focus on several important aspects: 1. Basic understanding of entrepreneurship: Santri are taught about the basic concepts of entrepreneurship, including how to identify business opportunities, plan a business, and understand the risks involved. This knowledge becomes a strong foundation for them to start a business, 2. Digital Marketing Strategy: In an increasingly connected world, digital marketing is the key to reaching customers. This training covers marketing techniques via social media, email and other digital platforms, which enable students to promote their products effectively, 3. Use of Online Platforms for Product Sales: Students are taught how to use various e-commerce and social media platforms to sell their products. This includes account creation, inventory management, and competitive pricing strategies. It is hoped that the results of this training can improve students' entrepreneurial skills and encourage them to be more creative in developing digital-based independent businesses. With the skills acquired, students will not only be able to start their own businesses, but also have the potential to create jobs for other people in their community.